Visions of quality how evaluators define, understand and represent program quality - Lloyd, Claire; Benson, Alexis; Hinn, D. Michelle (Greenwich, Conn. ; London : JAI, 2001)
The field of programme evaluation is shaped by an ever-increasing range of approaches each of which, to varying degrees, reflects evaluation's dual role as a theoretical endeavour and a form of socio-political inquiry. There is an array of approaches, each emphasizing different purposes and endorsing different methodologies to guide practice. Yet, no matter which goals are pursued and which methods are employed, all evaluation involves an effort to conceptualize, comprehend, and convey the quality of the programme. This volume brings together the work of certain evaluators to explore the evaluation of programme quality. Through conceptual descriptions and applied examples they discuss the theoretical concerns and practical issues that give rise to their particular conceptions of quality, the methodologies they employ to pursue an understanding of these conceptions, and the representational forms they employ to convey their understanding to stakeholders.
Description based on print version record.
Keywords: Educational evaluation; Curriculum evaluation; Curriculum planning & development; Education -- Curricula